On the taxonomic status of the Thai endemic freshwater snake Parahelicops boonsongi, with the erection of a new genus (Squamata: Natricidae) - David, Patrick; Pauwels, Olivier S. G.; Nguyen, Truong Quang; Vogel, Gernot (Zootaxa, 2015)
Parahelicops boonsongi Taylor & Elbel, 1958 is known from only three specimens from Thailand. It has been placed either in the genus Parahelicops Bourret, 1934, along with Parahelicops annamensis Bourret, 1934, or in the genus Opisthotropis Günther, 1872. We compared its morphological characters with those of P. annamensis and with three other relevant genera, Opisthotropis, Pararhabdophis Bourret, 1934, and Paratapinophis Angel, 1929. Parahelicops boonsongi is phenotypically distinct from Parahelicops annamensis, Opisthotropis, and all other natricine genera. We consequently erect a new genus, Isanophis gen. nov., to accommodate Parahelicops boonsongi.